The Textual Outlaw: Reading John Rechy in the 21 st. century - Martín-Rodríguez, Manuel M. (Universidad de Alcalá. Servicio de Publicaciones, 2015)
More than fifty years after his literary debut, John Rechy continues fascinating readers and critics. The Textual Outlaw: Reading John Rechy in the 21st Century is the first critical volume completely devoted to the analysis of his works. Scholars from eight different academic institutions have collaborated to offer a rich and provocative collection that addresses such major questions as sexual identities, ethnicity, Chicanismo, urban geographies, queer subjectivities, autobiographical discourse, the gothic, intertextuality, the decolonial imaginary, reading, and reception. John Rechy contributes an essay on Real People as Fictional Characters, as well as a thorough interview discussing his literary career. A must read for the fields of Literature, Queer Studies, Chicano/a Studies, and Gender and Sexuality, among others.